The interface between task-modality and the use of previously known languages in young CLIL English learners - Martínez-Adrián, María; Arratibel-Irazusta, Izaskun (Studies in Second Language Learning and Teaching, 2020)
This article contributes to the scarcity of research on the interface between task-modality and the use of previously known languages (PKL) in young learners. It examines the use of Basque/Spanish by CLIL learners (aged 10-11) during oral interaction while completing two collaborative tasks in English: a speaking task and a speaking + writing task. Findings indicate that these learners are extensive users of their PKL. Task-modality is particularly evident in the case of amount of PKL use, as a higher number of PKL turns are obtained in the speaking + writing task. However, task-modality has a limited effect on the functions of PKL, which contrasts with previous studies with adults. Despite the extensive use of their PKL, these young and low-proficient learners employ them as cognitive tools that facilitate the organization of the tasks, the co-construction of meaning and the attention to formal aspects of language such as mechanics.